Independent Curriculum Adaptation Strategy for Students' Cultural Diversity at Pendreh Village Junior High School - Muthi'ah, Shafa'; Suriansyah, Ahmad; Purwanti, Ratna (PARADIGMA : JURNAL ILMU PENGETAHUAN AGAMA, DAN BUDAYA, 2025)
Cultural diversity in educational settings requires adaptive and inclusive curriculum strategies to ensure equitable learning opportunities for all students. This study aims to analyze the adaptation strategies of the Independent Curriculum implemented by a junior high school in Pendreh Village to address the cultural heterogeneity of its student population. Employing a descriptive qualitative approach, data were collected through in-depth interviews, participatory observations, and document analysis. Thematic analysis was used to identify patterns and themes related to curriculum adaptation practices. The findings reveal that adaptation efforts were undertaken through three primary strategies: (1) systematic mapping of students’ cultural backgrounds, (2) differentiated instruction tailored to students' individual needs and characteristics, and (3) integration of local cultural values into school activities and learning processes. Despite several challenges, such as limited availability of culturally relevant learning resources and insufficient teacher training in culturally responsive pedagogy, collaborative efforts among schools, communities, and local stakeholders, coupled with the application of flexible teaching approaches, fostered an inclusive and contextually responsive learning environment. The study concludes that the success of curriculum adaptation in multicultural contexts relies heavily on culturally responsive planning and the professional development of teachers in managing socio-cultural dynamics within the classroom, particularly in remote and underserved areas. These insights contribute to the broader discourse on inclusive education and highlight the strategic importance of local culture in shaping equitable and effective learning experiences.